Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1001/jamadermatol.2020.2330
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life Assessed Using Skindex-16 Scores Among Patients With Acne Receiving Isotretinoin Treatment

Abstract: IMPORTANCEAcne is a common dermatologic condition and significantly affects psychosocial health and quality of life. An international task force recommended routine use of quality-of-life measures for clinic visits associated with acne management, but this has yet to translate into clinical practice.OBJECTIVE To assess mean Skindex-16 scores over time among patients with moderate to severe acne receiving isotretinoin treatment. DESIGN, SETTING, AND PARTICIPANTSA longitudinal, retrospective case series study of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
0
14
0
Order By: Relevance
“…30 Moreover, a recent retrospective study had reported an improvement in IGA after 2 month administration of oral isotretinoin and this study had expected approximately 4- to 5-fold improvements from baseline with a full course of isotretinoin. 31 …”
Section: Discussionmentioning
confidence: 99%
“…30 Moreover, a recent retrospective study had reported an improvement in IGA after 2 month administration of oral isotretinoin and this study had expected approximately 4- to 5-fold improvements from baseline with a full course of isotretinoin. 31 …”
Section: Discussionmentioning
confidence: 99%
“…PROMs provide a patient-centered perspective on treatment effectiveness and the importance of clear skin in dermatology [ 11 , 12 ]. For example, isotretinoin clinically meaningfully improves HRQL as measured by Skindex-16 [ 13 ]. PROMs can also help determine if prescribed medications are working properly (from the patient’s perspective) or causing significant side effects [ 14 ].…”
Section: Benefits Of Patient-reported Outcome Measures (Proms) In Cli...mentioning
confidence: 99%
“…In a study comparing DLQI, Short Form 36 (SF-36), and EuroQOL 5D (EQ-5D), DLQI was most responsive to changes in psoriasis treatments [ 36 ]. Additionally, acne patients receiving isotretinoin are more affected mentally than physically, and changes over time can be observed using Skindex-16 [ 13 ].…”
Section: Overview Of Psychometric and Practical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of RAR‐γ in the skin is more specific than that of the other subtypes. All‐trans retinoic acid (ATRA/tretinoin) is a commonly used RAR agonist in the clinical treatment of photoaging and skin inflammation‐related diseases, such as acne and psoriasis (di Masi et al, 2015; Mukherjee et al, 2006; Secrest et al, 2020). ATRA regulates proliferation, inflammation and immunity and promotes collagen production.…”
Section: Introductionmentioning
confidence: 99%